1D nanorod-like LiNi0.8Co0.1Mn0.1O2 as a cathode material for Li-ion batteries - Li, Yiming (Nanyang Technological University, 2019)
Li-ion batteries has been widely used in industry and recently there is an increasing demand for more efficient battery technologies. Among some of common cathode materials such as LCO, LNO and NCA, NCM offers many advantages and is considered as a promising candidate for next-generation cathode material. In my final year project, 811-type NCM material LiNi0.8Co0.1Mn0.1O2 was synthesized from MC2O4∙2H2O using a co-precipitation method. SEM and XRD analysis was performed to show the successful synthesis of high-purity LiNi0.8Co0.1Mn0.1O2 with a nanorod-like morphology. Subsequently LiNi0.8Co0.1Mn0.1O2 was used as cathode active material and coin cells were fabricated to perform electrochemical characterizaiton. To optimize the electrochemical performance, 3 sets of pararameters were investigated and their effects on electrochemical performance were discussed. Ratio of solvents, calcination temperature and calcination atmosphere were found to be closely related to morphology and electrochemical performances. With the optimum combination of parameters, NCM coin cells showed an excellent initial discharge specific capacity of 195 mAh g-1 at 0.1C. My work in this project could be used as a guide for further analysis.